2023
DOI: 10.3389/fpsyt.2022.1064141
|View full text |Cite
|
Sign up to set email alerts
|

ADHD in the DSM-5-TR: What has changed and what has not

Abstract: In this article, we critically review the changes made to the DSM-5 Text Revision published in 2022 regarding the diagnostic entity of Attention Deficit/Hyperactivity Disorder (ADHD). We structure our critique around three points. The first discusses the acknowledgment of ADHD as a neurodevelopmental disorder. The second examines the definition of ADHD provided in the updated edition of the manual. The third scrutinizes the changes in the diagnostic criteria for ADHD and assesses whether these changes make the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The existing diagnostic criteria for ADHD, rooted in subjective reports and clinical presentations, demonstrate high sensitivity, making it challenging to discern definitive pathology from ordinary variations [24]. In recent studies, researchers suggested that the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria lead to over-diagnosis, with lower clinical thresholds than the previous DSM criteria [25].…”
Section: Pathophysiology and Diagnosis Of Adhd And Narcolepsymentioning
confidence: 99%
“…The existing diagnostic criteria for ADHD, rooted in subjective reports and clinical presentations, demonstrate high sensitivity, making it challenging to discern definitive pathology from ordinary variations [24]. In recent studies, researchers suggested that the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria lead to over-diagnosis, with lower clinical thresholds than the previous DSM criteria [25].…”
Section: Pathophysiology and Diagnosis Of Adhd And Narcolepsymentioning
confidence: 99%
“…Some experts do feel the change in diagnostic criteria did not have a sound scientific base [16]. The concern was not just about influence from the pharma lobby, but from parents who felt their children had ADHD and needed easier access to medication [17]. Not every child with attentional difficulty has ADHD.…”
Section: Classification and Diagnosis In Psychiatry: Insights Into Po...mentioning
confidence: 99%
“…The diagnostic criteria for ADHD in the DSM-5-TR remained identical to those in the previous edition. Koutsoklenis and Honkasilta [7] make a critique of these criteria, concluding that they are ambiguous, redundant, and arbitrary, reinforcing normality and inadequate attention to context.…”
Section: Of 14mentioning
confidence: 99%